2021
DOI: 10.3389/fpsyg.2021.737882
|View full text |Cite
|
Sign up to set email alerts
|

Negative Perception of the COVID-19 Pandemic Is Dropping: Evidence From Twitter Posts

Abstract: The COVID-19 pandemic hit hard society, strongly affecting the emotions of the people and wellbeing. It is difficult to measure how the pandemic has affected the sentiment of the people, not to mention how people responded to the dramatic events that took place during the pandemic. This study contributes to this discussion by showing that the negative perception of the people of the COVID-19 pandemic is dropping. By negative perception, we mean the number of negative words the users of Twitter, a social media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 117 publications
0
8
0
1
Order By: Relevance
“…In the early days of the pandemic, serious concerns about contracting the COVID-19 virus led to a long hesitation period for passengers to resume their usual air travel plans. However, evidence from social media indicated that negative perceptions of COVID-19 changed with the start of the vaccination campaign [ 53 ]. Eighty-six percent of China's population is fully vaccinated with the last dose of the primary series, which is among the highest vaccination rates in the world (WHO data, https://covid19.who.int/table ).…”
Section: Discussionmentioning
confidence: 99%
“…In the early days of the pandemic, serious concerns about contracting the COVID-19 virus led to a long hesitation period for passengers to resume their usual air travel plans. However, evidence from social media indicated that negative perceptions of COVID-19 changed with the start of the vaccination campaign [ 53 ]. Eighty-six percent of China's population is fully vaccinated with the last dose of the primary series, which is among the highest vaccination rates in the world (WHO data, https://covid19.who.int/table ).…”
Section: Discussionmentioning
confidence: 99%
“…For political communication on Twitter, the COVID-19 pandemic provides an intriguing scenario to examine the generalizability of our findings in different contexts. Research on sharing behavior of COVID-19 news mostly focuses on the transmission of negative emotions and misinformation (e.g., Lăzăroiu and Adams, 2020;Kim and Florack, 2021;Vargas et al, 2021;Kim et al, 2022). Only a few studies have investigated how positive emotions like hope or optimism are shared during the COVID-19 pandemic (Nanath and Joy, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The words were classified as positive or negative using a sentiment analysis program. Similar sentiment analysis tools are frequently used to investigate the influence of emotional content on social networks (e.g., Vargas et al, 2021). Furthermore, a wide range of machine learning and deep learning methods exist to study predictors of sharing behavior (e.g., Zhang et al, 2016;Wang and Yang, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent study ( Vargas, Maier, Vallim, Banda, & Preciado, 2021 ) explored how COVID-19 has affected people from a psychophysical point of view. The analysis of the tweet led the authors to affirm that vaccination played a fundamental role in reducing people’s negativity by promoting their psychological well-being.…”
Section: Related Literaturementioning
confidence: 99%